TAX KNOWLEDGE, IMPLEMENTATION OF E-FILING, AND INTEGRATION OF NIK INTO NPWP ON TAXPAYER COMPLIANCE - Sartika, Mia Dwi; Purwaningsih, Eny (JURNAL EMA (Ekonomi Manajemen Akuntansi), 2025)
This study aims to analyze the impact of tax service quality, the implementation of e-filing, and the integration of the Population Identification Number (NIK) into the Taxpayer Identification Number (NPWP) on taxpayer compliance in Indonesia. The background of this research highlights the importance of improving taxpayer compliance to boost state revenue from the tax sector, which is essential for national development funding. High-quality tax services, the convenience of e-filing for electronic tax reporting, and the integration of NIK into NPWP are expected to ease the tax compliance process, thus enhancing taxpayer adherence. The research employs a quantitative method with data collected through a questionnaire distributed to 54 employees registered as taxpayers at PT Industrial Multi Fan, West Jakarta. The collected data are analyzed using multiple linear regression to assess the impact of the independent variables on taxpayer compliance. Results indicate that all three independent variables—tax service quality, e-filing implementation, and NIK integration—positively and significantly influence taxpayer compliance. Quality tax service improves taxpayer comfort and satisfaction, e-filing enhances reporting efficiency, and NIK integration simplifies administrative processes, thereby reducing errors and increasing compliance.